Implementation of Junior High School Individual Counseling Services in Medan City - Sari, Putri Mayang; Sinaga, M. Harwansyah Putra; Pradhana, Poetriku; Saragih, Ulfa Khairani (Universitas Islam Negeri Raden Intan Lampung, 2023)
Individual counseling service activities are one of the guidance and counseling services practiced by teachers (counselors) in schools to help solve student problems (counselees). Therefore individual counseling services must be carried out properly and have a positive value. This study aims to determine the extent to which the implementation of individual counseling services for junior high schools in the city of Medan is viewed from several aspects of the implementation of individual counseling services provided by guidance and counseling teachers at schools. The research method used is a quantitative descriptive approach with a survey design. Data collection instruments are interviews, observation, documentation and questionnaires. The subjects of this study were guidance and counseling teachers at junior high schools in the city of Medan. As for the results, it can be seen that the implementation of individual counseling services is a service that is often used by guidance and counseling teachers. Based on the results of this study it can be concluded that junior high school guidance and counseling teachers in Medan City choose individual counseling services as a good service in alleviating student problems at school, with a success rate of solving student problems from 61% to 100%.